Introduction to Special Section on 'police reform and human rights in the Western Balkans’ - Collantes-Celador, Gemma; Schwandner-Sievers, Stephanie (Taylor & Francis, 2019)
Throughout the Western Balkans a range of international actors have been involved in the comprehensive reconstruction of polities, economies and societies ravaged by the violent conflicts and political turmoil of the 1990s. The reform of police forces in accordance with international policing and human rights standards and practices has played a crucial role in the wider peace- and state-building efforts. To international proponents of liberal democratic governance, the police, alongside the judiciary and the penitentiary system, should serve as an important pillar of protecting human rights. Given a history of the police’s participation in the war efforts during Yugoslavia’s disintegration process as well as their role as henchmen of the previously ruling regimes, tackling the legacies of ethnic bias and human rights violations in the police forces appeared of utmost importance. Beyond this specific war-related necessity and guided by the concept of ‘democratic policing’, international-facilitated police reform processes in the Western Balkans – like in many other parts of the world – have aimed to turn the police into a ‘servant’ of citizens, not the state. This implies that the police forces should operate in an accountable, transparent and law-abiding manner in accordance with internationally and domestically agreed human rights standards. The envisaged result is the provision of security to all citizens equally, which in turn contributes to the improvement of domestic human rights practices and the emergence of a rule of law culture. But how effective have these endeavours been in practice? What lessons can we draw from efforts to implement democratic policing agendas in the Western Balkans?